Meta-Analysis of Puzzle Media in High School Lessons by Practicality Test - Aulia, Rahma; Fitri, Rahmadhani; Ristiono; Yogica, Relsas (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2024)
Learning media innovation requires educators to be able to create learning media by utilizing technology-based media to suit students' learning characteristics. Apart from that, the use of learning media used by teachers still does not support students' interest in the learning process. E-puzzle media can be used as a complement to innovative learning media so that it can stimulate students' creative thinking abilities. This research aims to collect similar articles from search results of several journals on internet sites. The sample used in this research was 10 articles related to e-puzzle development. This research method uses a meta-analysis method, where data collection techniques use statistical techniques that combine several studies related to puzzle development in biology learning collected via internet sites so that combined quantitative data is obtained. The research results found that the average level of practicality in using e-puzzles by teachers was 87.84% in the very practical category, while the average level of practicality by students was 86.51% in the very practical category. Based on the results of the practicality analysis, the e-puzzle developed can be categorized as practical so that it is suitable for use in the learning process.